2017
DOI: 10.3126/jfl.v15i1.23084
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Forest Management in Nepal: Tenure, Governance and Contestations

Abstract: Collaborative forest management (CFM) is a ‘community-based’ forest tenure regime that works in partnership between the central government, local government and local forest user groups in Nepal’s Terai, particularly in the management of large, contiguous forests. It has been in practice since the early 2000s in the form of ‘pilot initiatives’ and is gradually receiving greater legal attention. Through our own experiences, available literature and review of policies, we document the evolutionary history of Ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 9 publications
(9 reference statements)
0
11
0
Order By: Relevance
“…Since stakeholders have witnessed events where the conventional techno-bureaucratic authority has constrained the autonomy of FUGs [28,[62][63][64], stakeholders suspect that the implementation of SciFM will herald the revival of recentralized forest management. Further, the productive, high-value forests of Nepal's Tarai have always been a focus of conflict [65][66][67] among the stakeholders due to their diverse interests being dominated by political and economic considerations and motivations. Cases from community forests implementing SciFM have revealed that forest management decisions under SciFM are predominantly guided by the forest administration [29].…”
Section: Potential Reasons and Implications Of Differences In Conceptmentioning
confidence: 99%
“…Since stakeholders have witnessed events where the conventional techno-bureaucratic authority has constrained the autonomy of FUGs [28,[62][63][64], stakeholders suspect that the implementation of SciFM will herald the revival of recentralized forest management. Further, the productive, high-value forests of Nepal's Tarai have always been a focus of conflict [65][66][67] among the stakeholders due to their diverse interests being dominated by political and economic considerations and motivations. Cases from community forests implementing SciFM have revealed that forest management decisions under SciFM are predominantly guided by the forest administration [29].…”
Section: Potential Reasons and Implications Of Differences In Conceptmentioning
confidence: 99%
“…The idea of conflict transformation is in line with the perspectives of dynamic power/authority, which suggests mutually shared roles to all the parties. Such perspectives of power/authority considers forest tenure conflicts as a result of unbalanced power relations among the relevant parties in forest tenure (Bodin, 2017;Dhungana et al, 2017;Evans et al, 2008;Maring, 2010;Ratner et al, 2017;Suporahardjo, 2005). Achieving a dynamic yet balanced set of power relations began with each party openly articulating their interests as a basis for collaboration, which was supported through the creation of a common goal, and consistently implemented through control mechanisms (Adu et al, 2015;Maring, 2013;Ratner et al, 2014;Sumanto, 2009).…”
Section: Communication Of Multi-stakeholder Interests and Multi-stakeholder Facilitation Supportmentioning
confidence: 99%
“…The journal entry uncovered that basic level teachers decided on their pedagogical approaches. That motivated us to create a better decision-making space, where every member could share benefits equally (S. P. Dhungana et al, 2017). We began to explore ways that we could make space for all researchparticipants to experience equal benefits from collaborative practices.…”
Section: Cross-professional Collaborationmentioning
confidence: 99%